Mandated sick pay: Coverage, utilization, and welfare effects - Catherine Maclean; Stefan Pichler; Nicolas R. Ziebarth (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
This paper evaluates how sick pay mandates operate at the job level in the United States. Using the National Compensation Survey and difference-in-differences models, we estimate their impact on coverage rates, sick leave use, labor costs, and non-mandated fringe benefits. Sick pay mandates increase coverage significantly by 18 percentage points from a baseline level of 66% in the first two years. Newly covered employees take two additional sick days per year. We find little evidence that mandating sick pay crowds-out non-mandated fringe benefits. Finally, we develop a model of optimal sick pay provision and illustrate the trade-offs when assessing welfare.
Keywords: I12; I18; J22; J28; J32; J38; J88; H75; 330; sick pay mandates; take-up; social insurance; fringe benefits; moral hazard; unintended consequences; medical leave; National Compensation Survey; optimal social insurance; Baily-Chetty; welfare